2015
DOI: 10.1080/15384047.2015.1040952
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemic tumor microenvironment induces perineural invasion in pancreatic cancer

Abstract: Glucose intolerance and frank diabetes mellitus (DM) can increase the risk of cancer death for pancreatic cancer (PanCa). However, the mechanism by which these factors influence cancer deaths is not clear. In this study, we established a model system to mimic the pancreatic tumor microenvironment in patients with DM to examine the biological behavior of PanCa cells and nerves in cell culture and in animals. Our in vitro studies demonstrated that hyperglycemia promoted the proliferation and invasion of PanCa ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…Diabetes mellitus improves following pancreatectomy, suggesting that diabetes may be induced by pancreatic cancer (6). Our previous studies confirmed that a hyperglycemic condition could promote the proliferation, invasion, epithelial-mesenchymal transition (EMT) as well as the metastasis of pancreatic cancer (7,8).…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…Diabetes mellitus improves following pancreatectomy, suggesting that diabetes may be induced by pancreatic cancer (6). Our previous studies confirmed that a hyperglycemic condition could promote the proliferation, invasion, epithelial-mesenchymal transition (EMT) as well as the metastasis of pancreatic cancer (7,8).…”
Section: Introductionmentioning
confidence: 54%
“…Hyperglycemic conditions could worsen the prognosis of pancreatic cancer by enhancing invasive ability and promoting epithelial-mesenchymal transition (EMT) through the production of hydrogen peroxide (8). In addition, diabetes mellitus was also found to enhance perineural invasion in pancreatic cancer patients and to aggravate a poor prognosis (7). It has been verified that the addition of 5.5 and 25 mM glucose resulted in balanced osmotic pressure inside and outside the cell membrane (21), thus we used 5.5 and 25 mM of glucose as it has been applied worldwide in the related field as a classical high glucose model in the cell culture.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ability of the enzyme to augment insulin/insulin-like growth factor 1 receptor signaling (76,77), along with the well-documented hyperinsulinemia in PDAC patients [either in the setting of new inset or longstanding diabetes (3,8,9)], suggests that in heparanase-rich PDAC microenvironment insulin is expected to induce stronger pro-tumorigenic response. Thus, heparanase induction appears to be a part of the mechanism(s) through which diabetic state promotes PDAC and renders it highly aggressive, therapyresistant and associated with particularly poor prognosis (3,4,(10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, positive association was reported between PDAC and insulin resistance/hyperinsulinemia (3,8,9). Conversely, recent reports suggest that diabetic state promotes PDAC and renders it highly aggressive, resistant to the existing therapies, and is associated with extremely poor prognosis (3,4,(10)(11)(12). Hence, PDAC and diabetes exhibit a unique bidirectional relationship, with diabetes being both an effect and etiological factor of the pancreatic cancer (3,4,11).…”
Section: Introductionmentioning
confidence: 99%
“…10 KRAS further induces abnormal mitochondrial metabolism and enhance glycolysis, with alterations in glutamine and lipid metabolism. 14 As extrinsic factors, the acidic and oxygen/nutrient-deprived microenvironment also induces cancer cells to reprogram their metabolic pathway and exploit the ability of cancerassociated fibroblasts and immunocytes to communicate, thereby adapting to metabolic stress. 14 Secreted products of these cells may be used as biomarkers.…”
Section: Sweet Predictions Speak Volumes For Early Detection Of Pancrmentioning
confidence: 99%